Synthesizing The Evidence Of Practice Research The Impact Of Nursing Care On Patients’ Safety; Systematic Review (Journal of Namibian Studies : History Politics Culture, 2022)
Background: Patient safety is a paramount concern in healthcare, with nursing care interventions serving as pivotal elements in ensuring positive patient outcomes and minimizing adverse events. Understanding the intricate relationship between nursing care and patient safety is crucial for optimizing healthcare quality and enhancing overall patient well-being.Aim: The aim of this study is to systematically synthesize evidence from practice research to comprehensively investigate the impact of nursing care interventions on various aspects of patient safety outcomes across diverse healthcare settings, providing valuable insights for healthcare practitioners, policymakers, and researchers.Method: Employing a rigorous systematic review and meta-analysis approach, this study systematically reviewed relevant literature spanning from 2017 to 2022. Databases including PubMed, MEDLINE, CINAHL, Cochrane, and Scopus were meticulously searched using predefined search syntaxes tailored to each database, ensuring comprehensive coverage of relevant studies.Results: The exhaustive database search yielded a total of 1,989 studies. Following meticulous screening and selection processes, 10 studies were deemed eligible for inclusion in the synthesis. The synthesized evidence from these studies revealed a significant association between nursing care interventions and patient safety outcomes, with various interventions demonstrating positive impacts in reducing adverse events, medication errors, and overall improving patient safety.Conclusion: The findings of this study underscore the paramount importance of nursing care interventions in promoting patient safety across diverse healthcare settings. By systematically synthesizing evidence from practice research, this study contributes to a deeper understanding of the complex relationship between nursing care and patient safety, providing actionable insights for healthcare practitioners, policymakers, and researchers to optimize healthcare quality and enhance patient outcomes.